Analisis Kualitas Daya dan Rekomendasi Perbaikan Sistem Kelistrikan di Gedung Perhotelan - Ahmad Hermawan; Jamik Apriliasari; Chandra Wiharya (Elposys: Jurnal Sistem Kelistrikan, 2023)
Fave Hotel is supplied by 2 PLN transformers, with capacities of 250 kVA and 100 kVA. The supply of electrical energy at Fave Hotel is very important because the possibility of disruption is very large in the process of distributing electrical energy. Load variations at Fave Hotel will also affect the electrical system. One of the disturbances that occur in the electric power system is power quality. The research method used is data observation, monitoring, analysis, and simulation using ETAP software. Based on the results of the analysis of various power quality parameters that were measured, the power quality conditions of the fave hotel were not good. A power quality problem has been identified at Fave Hotel, specifically a voltage imbalance occurs at MDP 2 on weekend is 2.64%. In addition, there is also a current imbalance occurs at MDP 1 and 2 during both weekends and weekdays, with the largest current imbalance occurs at MDP 2 on weekdays is 64.15%. To overcome the problem of voltage imbalance and current imbalance, it is recommended to perform load balancing on the system or install compensating equipment such as a voltage compensator.